2012
DOI: 10.2166/washdev.2012.043
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the solar water disinfection (SODIS) method by decreasing turbidity with NaCl

Abstract: Abstract.Solar water disinfection (SODIS) has proven to be effective at reducing diarrheal incidence in epidemiological intervention studies. However, the SODIS method is limited to waters of low turbidity (<30NTU). This study investigates the use of common table salt (NaCl) to reduce the turbidity of water containing suspended colloidal clay particles for use in the SODIS method. Three representative clays found in tropical soils (kaolinite, illite, and bentonite) were tested at three levels of turbidity (50,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 20 publications
1
20
0
Order By: Relevance
“…However, at the household level in developing countries, the high cost of conventional coagulants such as alum and ferric salts, or a lack of availability of natural coagulants such as Moringa Oleifera, often makes coagulation-flocculation an impractical option (Sobsey 2002). The flocculating behavior of different types of clay in aqueous solutions containing NaCl has been explored (Hsi & Clifton 1960;Gibbs 1983Gibbs , 1985Akther et al 2008;Panayiotopoulos et al 2004;Dawney & Pearce 2012). The use of NaCl as a means of reducing turbidity prior to SODIS treatment was examined by Dawney and Pearce (2012), when it was shown that NaCl in combination with sodium bentonite (a high-activity clay) can significantly reduce turbidity to as low as 4 NTU.…”
Section: Sodium Chloride (Sodis) As a Coagulantmentioning
confidence: 99%
See 2 more Smart Citations
“…However, at the household level in developing countries, the high cost of conventional coagulants such as alum and ferric salts, or a lack of availability of natural coagulants such as Moringa Oleifera, often makes coagulation-flocculation an impractical option (Sobsey 2002). The flocculating behavior of different types of clay in aqueous solutions containing NaCl has been explored (Hsi & Clifton 1960;Gibbs 1983Gibbs , 1985Akther et al 2008;Panayiotopoulos et al 2004;Dawney & Pearce 2012). The use of NaCl as a means of reducing turbidity prior to SODIS treatment was examined by Dawney and Pearce (2012), when it was shown that NaCl in combination with sodium bentonite (a high-activity clay) can significantly reduce turbidity to as low as 4 NTU.…”
Section: Sodium Chloride (Sodis) As a Coagulantmentioning
confidence: 99%
“…The flocculating behavior of different types of clay in aqueous solutions containing NaCl has been explored (Hsi & Clifton 1960;Gibbs 1983Gibbs , 1985Akther et al 2008;Panayiotopoulos et al 2004;Dawney & Pearce 2012). The use of NaCl as a means of reducing turbidity prior to SODIS treatment was examined by Dawney and Pearce (2012), when it was shown that NaCl in combination with sodium bentonite (a high-activity clay) can significantly reduce turbidity to as low as 4 NTU. In particular, the application of this technology to water that is to be used for hygiene and sanitation purposes shows promise, as the sodium content remaining in the supernatant is not as limiting (Dawney & Pearce, 2012).…”
Section: Sodium Chloride (Sodis) As a Coagulantmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been various methods attempted to provide drinking water in rural areas of undeveloped nations using solar technologies, including: (i) solar desalination; (ii) solar detoxification; and (iii) solar disinfection [7,8]. These methods include the use of basic solar stills [9,10], solar stills with improved output from compound parabolic reflectors [11], phase change material [12], a hemispherical solar still [13], efficient heat exchange mechanisms [14] and an inclined wick solar still [15], and progressively more sophisticated variations of the solar water disinfection (SODIS) method [16], using common chemicals to decrease turbidity to enable SODIS to work [17] and photocatalysts [18]. SODIS is low-cost, simple, and is available for large geographic regions (e.g., from Haiti [19] to South Sudan [20]), but becomes less effective in high-turbidity water, which can be challenging in some communities [16].…”
Section: Introductionmentioning
confidence: 99%
“…The more turbid solutions of bentonite, which flocculated more easily than the other clays, required less salt (1,000 mg/L) to achieve the same; the greater proximity of the clay particles to one another makes flocculation easier. The more turbid kaolinite and illite suspensions required the addition of a bentonite “jumpstarter” in order to be brought below the SODIS threshold 4 . None of the treated samples in the study had salt concentrations below the taste threshold of 256 mg/L, but several had less residual salt than a typical sports drink.…”
mentioning
confidence: 98%